Effect of Long-Term Ketogenic Diet in Mice Serum Adiponectin - Kurniasari, Hamidah; Rejeki, Purwo Sri; Kahar, Hartono; Sunarti, Sri (Folia Medica Indonesiana, 2022)
Highlight: • Adiponectin is an important protective factor for cardiovascular disease and increased insulin sensitivity. • Ketogenic diet effect on adiponectin level in mice besides decrease weight gain was determined. • The difference in serum adiponectin level and body weight is uncorrelated. Abstract: Ketogenic diet is a popular diet to reduce weight gain quickly. This diet has become a lifestyle . The ketogenic diet has been reported to affect adiponectin level, although it is still contraindicated. Adiponectin is a biomarker for metabolic disease that plays an important role as a protective factor for cardiovascular disease and increase insulin sensitivity. This study aimed to explore the effect of the ketogenic diet on adiponectin level in mice, besides decrease weight gain. This study was an experimental laboratory study with a randomized post-test-only control group design. Fourteen male mice (20-30 g) aged 2-3 months were divided randomly into K1 (n=7, standard diet) and K2 (n=7, ketogenic diet), were given diet for eight weeks, ad libitum. Body weight was measured at the pre and post-intervention, whereas adiponectin level were measured at the post-intervention using ELISA. The statistical analysis using SPSS version 16. The Shapiro Wilk test was used to determine normality, Independent T-Test was used to determine mean difference for normal distribution, Mann Whitney Test was used to determine mean difference for abnormal distribution, and Pearson Correlation was used to determine correlation. Difference (âˆ†) of body weight on K1 (12.00±6.26) g, K2 (1.29±7.41) g with p=0.02. Serum adiponectin level of K1 (0.082±0.014) µg/ml and K2 (0.096±0.008) µg/ml with p=0.035. This study showed ketogenic diet-induced higher serum adiponectin level and slower weight gain. There is no correlation between the difference in body weight and serum adiponectin level (p=0.403).